Big Ideas for a Small Planet - Season 1 Episode 1-13 - Redford, Robert (Arts Alliance America, 2008)
"Big Ideas for a Small Planet" is a documentary series presenting the forward-thinking designers, products and provesses that are at the forefront of a new green world. Each episode revolves around a different green theme as it spotlights 3 specific innovators or innovations that have the potential to transform out everyday lives. The indivials profiled range from scientists to fashion and product designers, and from entrepreneurs to first-time inventors. [Cover]